2010
DOI: 10.1080/10913671003715540
|View full text |Cite
|
Sign up to set email alerts
|

Pedometer Accuracy in Elementary School Children while Walking, Skipping, Galloping, and Sliding

Abstract: The purpose of this study was to examine the accuracy of the SW-701 (Yamax Corporation, Tokyo, Japan) and NL-800 (New-Lifestyles, Inc., Lee's Summit, Missouri, USA) pedometer in fifth-grade students while walking, skipping, galloping, sliding, and hopping. Counts registered by both pedometer models were significantly lower than actual counts while skipping, galloping, and sliding, and counts from the NL-800 were significantly lower than the SW-701 during these same movements. No significant differences in step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…A recent study investigating the accuracy of step counts in a pedometer that uses the same internal mechanism as the NL-1000 (NL-800) supported the notion that the mode of activity is an important determinant of pedometer accuracy (17). The latter authors observed significant underestimation of step counts (compared with a hand counter) when children were skipping, galloping, and sliding, with acceptable performance during walking and hopping.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study investigating the accuracy of step counts in a pedometer that uses the same internal mechanism as the NL-1000 (NL-800) supported the notion that the mode of activity is an important determinant of pedometer accuracy (17). The latter authors observed significant underestimation of step counts (compared with a hand counter) when children were skipping, galloping, and sliding, with acceptable performance during walking and hopping.…”
Section: Discussionmentioning
confidence: 94%
“…Παλαιότερες έρευνες είχαν μελετήσει την ακρίβεια και εγκυρότητα καταγραφής βημάτων κυρίως μηχανικών βηματομετρητών σε παιδιά και εφήβους (e.g. Duncan, Schofield, Duncan, & Hinckson, 2007;Hart, Brusseau, Kulinna, McClain, & Tudor-Locke, 2011;Nakae, Oshima, & Ishii, 2008;Smith & Schroeder, 2010 (Nakae, Oshima, & Ishii, 2008). Όσον αφορά έρευνες σε ενηλίκες, η πλειοψηφία αυτών έχει καταλήξει στο συμπέρασμα ότι οι νέες συσκευές (π.χ.…”
Section: σχολιασμός και σύγκριση αποτελεσμάτων καταγραφής βημάτων με προηγούμενες έρευνεςunclassified